Timing of repair of blunt thoracic aortic injuries in the thoracic endovascular aortic repair era - Alarhayem, Abdul Q.; Rasmussen, Todd E.; Farivar, Behzad; Lim, Sungho; Braverman, Max; Hardy, David; Jenkins, Donald J.; Eastridge, Brian J.; Cestero, Ramon F. (Journal of vascular surgery, 2021)
Thoracic endovascular aortic repair (TEVAR) is the preferred operative treatment of blunt thoracic aortic injuries (BTAIs). Its use is associated with improved outcomes compared with open surgical repair and nonoperative management. However, the optimal time from injury to repair is unknown and remains a subject of debate across different societal practice guidelines. The purpose of this study was to evaluate national trends in the management of BTAI, with a specific focus on the impact of timing of repair on outcomes. Using the National Trauma Data Bank, we identified adult patients with BTAI between 2012 and 2017. Patients with prehospital or emergency department cardiac arrest or incomplete data sets were excluded from analysis. Patients were classified according to timing of repair: group 1, <24 hours; and group 2, ≥24 hours. The primary outcome evaluated was in-hospital mortality; secondary outcomes included overall hospital and intensive care unit length of stay. Multivariable logistic regression was performed to identify independent predictors of mortality. The analysis was completed for 2821 patients who underwent TEVAR for BTAI with known operative times. The overall mortality in the patient cohort was 8.4% (238/2821); 75% of patients undergoing TEVAR were repaired within 24 hours. Mortality was more than twofold greater in group 1 compared with group 2 (9.8% [207/2118] vs 4.4% [31/703]; P = .001). This mortality benefit persisted across injury severity groups and was independent of the presence of serious extrathoracic injuries. Logistic regression analysis, adjusting for age ≥65 years, Glasgow Coma Scale score ≤8, systolic blood pressure ≤90 mm Hg at admission, and serious extrathoracic injuries, showed a higher adjusted mortality in group 1 (odds ratio, 2.54; 95% confidence interval, 1.66-3.91; P = .001). The majority of patients with BTAI undergo endovascular repair within 24 hours of injury. Patients undergoing delayed repair have improved survival compared with those repaired within the first 24 hours of injury in spite of similar injury patterns and severity. In patients with BTAIs without signs of imminent rupture, delaying endovascular repair beyond 24 hours after injury should be considered. [Display omitted]